2000
DOI: 10.1515/cclm.2000.205
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Iron Status in Anemic Patients with Rheumatoid Arthritis Using an Automated Immunoturbidimetric Assay for Transferrin Receptor

Abstract: We have evaluated a newly introduced immunoturbidimetric transferrin receptor assay (IdeA TfR-IT, Orion Diagnostica, Finland) in healthy subjects and in a study population consisting of patients with rheumatoid arthritis and juvenile chronic arthritis. The IdeA TfR-IT assay was found to provide reproducible results which were in good agreement with the ELISA assays from Orion Diagnostica (IDeA-ELISA, correlation R2=0.8, n=102) and R&D systems (Quantikine TfR ELISA assay, correlation R2=0.95, n=39). The analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…Bhujade, Talmate, and Patil () suggested that decrease in Hb during arthritis may be ascribed to reduced erythropoiten level or lowered response of the bone marrow erythropoiten and destruction of red blood cells prematurely. Most cases of anemia in rheumatoid arthritis subjects could be as a result of the depletion of iron that is stored in the body (Punnonen et al, ). Iron deficiency may also be caused by inflamed synovial tissue preferring to take up iron (Giordano, Floravanti, Sancasciani, Marcolongo, & Borghi, ).…”
Section: Discussionmentioning
confidence: 99%
“…Bhujade, Talmate, and Patil () suggested that decrease in Hb during arthritis may be ascribed to reduced erythropoiten level or lowered response of the bone marrow erythropoiten and destruction of red blood cells prematurely. Most cases of anemia in rheumatoid arthritis subjects could be as a result of the depletion of iron that is stored in the body (Punnonen et al, ). Iron deficiency may also be caused by inflamed synovial tissue preferring to take up iron (Giordano, Floravanti, Sancasciani, Marcolongo, & Borghi, ).…”
Section: Discussionmentioning
confidence: 99%
“…This may be iron-deficiency anaemia resulting from gastrointestinal bleeding provoked by the use of NSAIDs, but around 60% of the time in RA patients, it is anaemia of chronic disease which is associated with the severity of the condition [102] [103]. In the latter case, there will be low levels of plasma iron despite packed iron stores [41].…”
Section: Iron Status In Arthritic Patientsmentioning
confidence: 99%
“…Despite the massive amounts of circulating ferritin, its saturation with iron molecules since AOSD is not associated with iron overload [40, 76, 77]. This has also been proven with the use of automated analyzers that measure the transferring receptors in the serum [78]. Moreover, since the serum-transferring receptor concentration is not altered in inflammatory states, it may be a more useful test than serum ferritin in assessing the iron stores in AOSD [79].…”
Section: Resultsmentioning
confidence: 99%